A Microfluidic Device Integrating a Glucose Sensor and Calibration Function for Cell-Based Assays - Laner Chen; Kenta Shinha; Hiroko Nakamura; Kikuo Komori; Hiroshi Kimura (Biosensors)
Microphysiological systems (MPS) incorporating microfluidic technologies offer improved physiological relevance and real-time analysis for cell-based assays, but often lack non-invasive monitoring capabilities. Addressing this gap, we developed a microfluidic cell-based assay platform integrating an electrochemical biosensor for real-time, non-invasive monitoring of kinetic cell status through glucose consumption. The platform addresses the critical limitations of traditional cell assays, which typically rely on invasive, discontinuous methods. By combining enzyme-modified platinum electrodes within a microfluidic device, our biosensor can quantify dynamic changes in glucose concentration resulting from cellular metabolism. We have integrated a calibration function that corrects sensor drift, ensuring accurate and prolonged short-term measurement stability. In the validation experiments, the system successfully monitored glucose levels continuously for 20 h, demonstrating robust sensor performance and reliable glucose concentration predictions. Furthermore, in the cell toxicity assays using HepG2 cells exposed to varying concentrations of paraquat, the platform detected changes in glucose consumption, effectively quantifying the cellular toxicity responses. This capability highlights the device’s potential for accurately assessing the dynamic physiological conditions of the cells. Overall, our integrated platform significantly enhances cell-based assays by enabling continuous, quantitative, and non-destructive analysis, positioning it as a valuable tool for future drug development and biomedical research.